WRKY2/34–VQ20 Modules in Arabidopsis thaliana Negatively Regulate Expression of a Trio of Related MYB Transcription Factors During Pollen Development - Lei, Rihua; Ma, Zhenbing; Yu, Diqiu (Frontiers in Plant Science, 2018)
Male gametogenesis in plants is tightly controlled and involves the complex and precise regulation of transcriptional reprogramming. Interactions between WRKY proteins and VQ motif-containing proteins are required to control these complicated transcriptional networks. However, our understanding of the mechanisms by which these complexes affect downstream gene expression is quite limited. In this study, we found that WRKY2 and WKRY34 repress MYB97, MYB101, and MYB120 expression during male gametogenesis. MYB expression was up-regulated in the wrky2-1 wrky34-1 vq20-1 triple mutant during male gametogenesis. The expression levels of six potential targets of the three MYBs increased the most in the wrky2-1 wrky34-1 vq20-1 triple mutant, followed by the wrky2-1 wrky34-1 double mutant, compared with in wild-type. Yeast one-hybrid and dual luciferase reporter assays indicated that WRKY2 and WRKY34 recognized the MYB97 promoter by binding to its W-boxes. MYB97 overexpression caused defects in pollen germination and pollen tube length, which impacted male fertility. Thus, WRKY2/34–VQ20 complexes appear to negatively regulate the expression of certain MYBs during plant male gametogenesis.